“No such Ordinary Gift Left”. The Struggle between Charismatic Healing and Institutional Religion in English Demonological Treatises (S. XVI-XVII) - Méndez, Agustín (Cuadernos de Historia Moderna, 2016)
This work aims to analyze the campaign against charismatic healers carried out by English demonologists between 1584-1627 as a particular episode in the tensions between charisma and institution that characterized Christian history. The next pages will try to demonstrate that reformed theologians attempted to eradicate wise folk because they challenged the theological orthodoxy of the official Church, but also because they threated the role they were trying to secure for themselves in society. Members of protestant high theological culture intended to devaluate cunning folk´s social position by associating them with diabolism and Catholicism, a rhetorical strategy that also aspired to evince reformed ideas as the only true and legitimate expression of Christianity
Keywords: Charisma; Cunning Folk; Demonology; Protestantism; Institution